The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.24840/2183-0606_011.001_0003
|View full text |Cite
|
Sign up to set email alerts
|

Brainport Eindhoven: born from crisis - 25 years as a Triple Helix Governed Ecosystem

Abstract: Various researchers have called for research into positive examples of successful triple helix governed ecosystems. Triple Helix collaborations are seen as the solution to tackle the current ‘wicked problems’ of society. Researchers are encouraged to enhance our understanding of governing inter-organizational collaborations (ecosystems) in the context of university-industry-government (Triple Helix) relations. In this paper we therefore describe a case study of the Brainport Eindhoven ecosystem in the Netherla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, other cytokines, namely IL-1RA and IL-8, were not detectable. 13 Other sampling techniques, such as skin blotting, have also reported an upregulation of IL-1α over the site of a PU, although these methods remain semiquantitative and require standardisation owing to the inflexibility of nitrocellulose membranes. 30 Indeed, in the present study, we have reported a significant upregulation of both IL-1α as well as the low abundant cytokines, IL-8, IL-1β, G-CSF, and a down-regulation of IL-1RA at the site of Stage I PU relative to that of the control site.…”
Section: Biomarker Methods To Determine Thresholdsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other cytokines, namely IL-1RA and IL-8, were not detectable. 13 Other sampling techniques, such as skin blotting, have also reported an upregulation of IL-1α over the site of a PU, although these methods remain semiquantitative and require standardisation owing to the inflexibility of nitrocellulose membranes. 30 Indeed, in the present study, we have reported a significant upregulation of both IL-1α as well as the low abundant cytokines, IL-8, IL-1β, G-CSF, and a down-regulation of IL-1RA at the site of Stage I PU relative to that of the control site.…”
Section: Biomarker Methods To Determine Thresholdsmentioning
confidence: 99%
“…Previous in-vitro studies, involving cell and tissue models, and animal studies have reported the release of cytokines following prolonged mechanical loading. 12,13 Non-invasive adhesive tapes have been used to sample cytokines typically IL-1α, IL-1RA, IL-8, INF-γ, and IL-6 from sebum on the skin surface. Subsequently, studies have shown their upregulation following prescribed mechanical and chemical insults, [14][15][16][17] as well as clinically relevant loads following the attachment of medical devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation